EXPLORING THE NEXUS BETWEEN WOMEN'S EMPOWERMENT PROGRAMS, EDUCATIONAL ATTAINMENT, AND AGE DIFFERENCES IN POVERTY ALLEVIATION IN NIGERIA - NNANA OKOI OFEM; TIKU ORU TAKIM; TANGBAN EGBE EBAGU; RITA NGOZI OKAFOR (International Studies Journal)
Poverty remains a pressing global challenge, particularly in developing nations like Nigeria. Women, constituting a significant proportion of those affected, encounter distinct challenges due to gender disparities and limited access to resources. The study aims to assess women's empowerment programs, educational attainment, and age disparities concerning poverty alleviation efforts in Nigeria within the diverse landscape of the Central Senatorial District. The study employed a qualitative research design, the study engaged 24 participants, ensuring diversity across age groups, educational backgrounds, and geographical locations. Through semi-structured interviews and two focus group discussions, each comprising six participants, the research collected rich and nuanced narratives. Thematic analysis served as the analytical lens, meticulously unraveling patterns and themes inherent in the participants' experiences. Three theories were used to support the study which includes empowerment theory, participatory model and social learning theory. Findings reveals that educational empowerment Impact," underscores how varying educational levels among women significantly influence their participation in and perceived benefits from empowerment initiatives. "Age Dynamics in Empowerment" sheds light on how age disparities shape women's interactions with these programs, indicating differing needs and outcomes across age groups. "Program Effectiveness and Accessibility" uncovers the participant’s effectiveness and accessibility of empowerment schemes "Societal and Cultural Influences" illuminates how societal norms and cultural factors intersect with program engagement, influencing women's experiences within these initiatives. The theme "Economic Opportunities and Livelihoods" underscores the significance of economic opportunities and livelihoods afforded by empowerment programs, impacting women's financial stability. Lastly, "Perceptions of Program Impact" captures the diverse perspectives regarding the actual impact of these programs on the lives of the women involved, showcasing varying degrees of positive and negative experiences and outcomes. The findings contribute substantively to the discourse on enhancing the effectiveness of empowerment programs, emphasizing the need for tailored interventions that consider educational backgrounds and age-specific needs to foster sustainable poverty reduction strategies among women.